2012
DOI: 10.1002/mnfr.201100680
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo structure and activity relationship analysis of polymethoxylated flavonoids: Identifying sinensetin as a novel antiangiogenesis agent

Abstract: The in vivo structure-activity relationship (SAR) analysis indicated that a flavonoid with a methoxylated group at the C3' position offers a stronger antiangiogenesis activity, whereas the absence of a methoxylated group at the C8 position offers lower lethal toxicity in addition to enhancing the antiangiogenesis activity. This study provides new insight into how modification of the chemical structure of polymethoxylated flavonoids affects this newly identified antiangiogenesis activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 36 publications
(42 reference statements)
2
51
0
Order By: Relevance
“…Nobiletin differs from sinensetin by having methylation at the C8 position. Together with previous research of nobiletin [55], structure-activity relationship analysis indicated that the absence of a methoxylated group at the C8 position offers lower lethal toxicity in addition to enhancing the antiangiogenesis activity via observing intersegmental vessel development in zebrafish embryos [54]. …”
Section: Anticarcinogenic Propertiesmentioning
confidence: 63%
See 1 more Smart Citation
“…Nobiletin differs from sinensetin by having methylation at the C8 position. Together with previous research of nobiletin [55], structure-activity relationship analysis indicated that the absence of a methoxylated group at the C8 position offers lower lethal toxicity in addition to enhancing the antiangiogenesis activity via observing intersegmental vessel development in zebrafish embryos [54]. …”
Section: Anticarcinogenic Propertiesmentioning
confidence: 63%
“…Sinensetin, which showed the most potent antiangiogenesis activity and the lowest toxicity, inhibited angiogenesis by inducing cell cycle arrest in the G0/G1 phase in HUVEC culture and downregulating the mRNA expressions of angiogenesis genes flt1 , kdrl , and hras in zebrafish [54]. Nobiletin differs from sinensetin by having methylation at the C8 position.…”
Section: Anticarcinogenic Propertiesmentioning
confidence: 99%
“…Noticeable anti-parasitic activity has been reported for flavones and related secondary metabolites such as flavanones, chalcones or catechins [22,24] and for semisynthetic analogs [28]. Nevertheless, with the exception of santin (8) [12], 5,7-dihydroxy-3,6-dimethoxyflavones have never been screened against this type of target.…”
Section: Anti-parasitic Activitymentioning
confidence: 96%
“…In this regard, Citrus flavonoids have been shown to target tumor angiogenesis. Lam et al [127] reported that hydroxylated PMFs suppressed the expression of VEGF and MMP-9 in colonic tumors. Sinensetin, a common PMFs found in Citrus fruits, which showed the most potent anti-angiogenesis activity and the lowest toxicity, inhibited angiogenesis by inducing cell cycle arrest in the G0/G1 phase in HUVEC culture and downregulating the mRNA expressions of angiogenesis genes fl1, kdrl, and hras in zebrafish.…”
Section: Anti-angiogenesismentioning
confidence: 99%